The inheritance of vowel phoneme of the proto Austronesia language in Tamiang language - Devi Pratiwy (Proceedings of AICS - Social Sciences, 2017)
As a Malay variant which belongs to the Austronesian group (PAN), Tamiang Language (TL for short) should have inherited various elements of its proto including phonemes. This paper is aimed to analyze the inheritance of Proto vowels in TL and the types of their changes. The source of data of TL is from 200 words included in Swadesh list as the references while collecting data. Data were collected by one-on-one interview which was conducted structurally (Creswell, 2009). Data then were recorded and noted phonemically. Data from the proto language were found out from the gloss in the Proto Austronesian Dictionary. The data was then analyzed following qualitative method. The result showed that most vowels in PAN inherited linearly in TL. However, some changes can also be recognized due to the phonetic environment or sporadic reasons. PAN*/i/ inherited linearly into /i/ in TL in initial, medial and final position of the word. However, sound change can also be recognized in */i/ /ǝ/ and /e/. PAN */u/ inherited linearly to /u/ in TL in medial and final position. Due to sporadic correspondence, */u/ changed into /i/, /ɔ/ and /o/. PAN */ǝ/ inherited regularly into /ǝ/ in TL in initial and medial position. However, */ǝ/ also changes into /a/. Then */a/ inherited into /a/ in initial and medial position, yet, in final position /a/ is contributed complementarily with /ǝ/. This change happened sporadically due to error in language use or the influence of other language toward TL.